2021
DOI: 10.1161/jaha.120.020190
|View full text |Cite
|
Sign up to set email alerts
|

Association of Daily Mean Temperature and Temperature Variability With Onset Risks of Acute Aortic Dissection

Abstract: Background The association between ambient temperature and cardiovascular diseases has been well established, but evidence of temporal changes in the risk of acute aortic dissection (AAD) onset is lacking. Methods and Results We conducted an 8‐year time‐series study based on data from 2120 patients diagnosed with AAD at Tongji Hospital (Wuhan, China). Daily meteorological parameters were measured in the study area. Spearman's rank correlation analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Nevertheless, the overall trend of the associations between cold weather and AAD onset in our study were consistent with previous ones. 5 , 6 , 9 , 10 , 24 In addition to low ambient temperature, we found temperature decline between two neighboring days was also associated with higher AAD onset. To the best of our knowledge, only one previous study has examined the associations of AAD onset with TCN besides absolute temperature, and the findings were consistent with ours.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, the overall trend of the associations between cold weather and AAD onset in our study were consistent with previous ones. 5 , 6 , 9 , 10 , 24 In addition to low ambient temperature, we found temperature decline between two neighboring days was also associated with higher AAD onset. To the best of our knowledge, only one previous study has examined the associations of AAD onset with TCN besides absolute temperature, and the findings were consistent with ours.…”
Section: Discussionmentioning
confidence: 72%
“… 6 , 7 , 8 , 9 Moreover, all previous studies lack the sub-daily information of AAD onset and therefore only examined the associations on a daily basis, which might attenuate the causality due to the unclear chronological order of exposure and events within the same day. 6 , 9 , 10 As the onset of AAD fluctuates greatly during 24-hours throughout a day, it is therefore critically important to evaluate the association between temperature and AAD onset at hourly level. In addition, AAD can be classified into type A (which occurs in the ascending aorta) and type B (which occurs in the descending aorta and distal arteries) based on the Stanford classification, which varied in symptoms, anatomical location, and fatality rate and thus might have different risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with existing studies, in the work of Yu et al, they found that extremely low ambient temperature is positively associated with the onset of AAD (Yu et al, 2021). In a study between incidence of AAD and climatic factors, it was found that the frequency of AAD reached its peak in winter (Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…The incidence rate of AAD was the highest in winter and the lowest in summer (Xia et al, 2020). A study has found that a low temperature environment can increase the risk of AAD (Yu et al, 2021), and a signi cant association between cold temperature and the AAD was discovered by a linear regression analysis (Sadamatsu et al, 2020). Seasonal variation suggests that ambient temperature may be an important environmental risk factor for AAD.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were limited by small study samples and show conflicting results [ 14–19 ]. Recently, however, two large studies using advanced statistical methods reported increased risk of acute aortic dissection at lower temperatures [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%